2011
DOI: 10.1590/s1516-80342011000200009
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre as restrições de participação em atividades de vida diária e o benefício do uso de próteses auditivas em adultos e idosos

Abstract: OBJETIVO: Estudar o benefício obtido com o uso de próteses auditivas em ambientes acusticamente favoráveis à comunicação, reverberantes, ruidosos e com sons aversivos e correlacioná-lo com as restrições de participação e limitações de atividades de adultos e idosos deficientes auditivos. MÉTODOS: Foram avaliados 42 indivíduos atendidos na instituição em que o estudo foi realizado. Estes responderam aos questionários Hearing Handicap Inventory for Elderly ou for Adults e Abbreviated Profile of Hearing Aid Benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 16 publications
1
11
1
5
Order By: Relevance
“…Some authors have stressed that the score assigned by patients can be related to their decision to purchase a hearing aid (8,27) . As for the values of HHIA and HHIE-S, the data collected in this study were different from those reported in previous studies, which reported an average of 45.9 ± 27 points for HHIA and 15.78 ± 18.03 points for HHIE-S (12,28) . The average score of HHIE-S showed a negative correlation when compared to VAS, prior to hearing aid use, that is, the lower the score a patient assigned to hearing before the use of a hearing aid, the more restricted their social participation was.…”
Section: Discussioncontrasting
confidence: 99%
“…Some authors have stressed that the score assigned by patients can be related to their decision to purchase a hearing aid (8,27) . As for the values of HHIA and HHIE-S, the data collected in this study were different from those reported in previous studies, which reported an average of 45.9 ± 27 points for HHIA and 15.78 ± 18.03 points for HHIE-S (12,28) . The average score of HHIE-S showed a negative correlation when compared to VAS, prior to hearing aid use, that is, the lower the score a patient assigned to hearing before the use of a hearing aid, the more restricted their social participation was.…”
Section: Discussioncontrasting
confidence: 99%
“…The use of hearing aid devices reduced the self-perception of restricted participation, as demonstrated by the results of HHIA/E ( Table 3). The positive impact of hearing aid usage in comparison to the perception of social and emotional disadvantages resulting from hearing loss was already reported in literature (24,25) .…”
Section: Discussionmentioning
confidence: 68%
“…It was observed also the cognitive decline rates and the risk of incident cognitive impairment were linearly related to the severity of hearing loss at study entry 38 . Although the prevalence of hearing loss and the functional limitations resulting therefrom are high in elderly, study shows that people who could benefit from a hearing aid, 89.3% do not possess 39 . In this study, only 1.7% of elderly made use of hearing aid.…”
mentioning
confidence: 92%